Functional relationship of particulate matter (PM) emissions, animal species, and moisture content during manure application. (October 2020) - Kabelitz, Tina; Ammon, Christian; Funk, Roger; Münch, Steffen; Biniasch, Oliver; Nübel, Ulrich; Thiel, Nadine; Rösler, Uwe; Siller, Paul; Amon, Barbara; Aarnink, André J.A.; Amon, Thomas
Graphical abstract: Highlights: PM is aerosolized when manure DM is >60% for poultry and >80% for pig. a high manure DM results in smaller particles and elevated PM emissions. maximum PM10 potential of pig and poultry manure is 1–3 kg t −1 of applied manure. survival of pathogenic bacteria in dried manure and in PM is strongly reduced. the optimal DM range is 55–70% for poultry manure and 75–85% for pig manure. Abstract: Livestock manure is recycled to agricultural land as organic fertilizer. Due to the extensive usage of antibiotics in conventional animal farming, antibiotic-resistant bacteria are highly prevalent in feces and manure. The spread of wind-driven particulate matter (PM) with potentially associated harmful bacteria through manure application may pose a threat to environmental and human health. We studied whether PM was aerosolized during the application of solid and dried livestock manure and the functional relationship between PM release, manure dry matter content (DM), treatment and animal species. In parallel, manure and resulting PM were investigated for the survival of pathogenic and antibiotic-resistant bacterial species. The results showed that from manure with a higher DM smaller particles were generated and more PM was emitted. A positive correlation between manure DM and PM aerosolization rate was observed. There was a species-dependent critical dryness level (poultry: 60% DM, pig: 80% DM) where manure began to release PM into the environment. The maximum PM emission potentials were 1 and 3 kg t −1 of applied poultry and pig manure, respectively. Dried manure and resulting PM contained strongly reduced amounts of investigated pathogenic and antibiotic-resistant microorganisms compared to fresh samples. An optimal manure DM regarding low PM emissions and reduced pathogen viability was defined from our results, which was 55–70% DM for poultry manure and 75–85% DM for pig manure. The novel findings of this study increase our detailed understanding and basic knowledge on manure PM emissions and enable optimization of manure management, aiming a manure DM that reduces PM emissions and pathogenic release into the environment.